Analysis of Atrium Pattern, Trombe Wall and Solar Greenhouse on Energy Efficiency - Modirrousta, Sama; Boostani, Haleh (Elsevier Science Bv, 2016)
One of the most lucrative renewable energy sources for supplying energy in future decades is the solar energy. Solar energy can be utilized through both active and inactive systems. Inactive solar systems are the ones which collect and store solar energy without the use of energy-consuming devises such as pumps or controllers, so that the energy can be used at the time of need. This causes the amount of energy consumption in different parts of a building to reach their point of minimum. There are different methods for the utilization of the solar energy in an inactive way, namely solar windows, solar greenhouse method, Trombe wall and aqua wall, atriums, and pools on the roof tops. In this paper, the most common methods of using solar energy in inactive ways, which are atriums, Trombe wall, and solar greenhouse are analyzed. The method of the research is descriptiveanalytic so that with better knowledge, modern designs can gain full benefit from these techniques. (C) 2015 The Authors. Published by Elsevier Ltd.
International Conference on Sustainable Design, Engineering and Construction (ICSDEC) -- MAY 18-20, 2016 -- Arizona State Univ, Coll Avenue Commons, Tempe, AZ
Keywords: Atrium; Inactive Systems; Solar Energy; Solar Greenhouse; Trombe Wall